The impact of osteoporosis on arthroscopic rotator cuff repair and postoperative tendon-to-bone healing - He, Junlong; Chen, Tao; Wu, Chenxi; Zhang, Kaijia; You, Peijie; Lai, Qilong; Jiang, Hong; Liu, Guanhong (Frontiers in Surgery, 2025)
This review explores the impact of osteoporosis on arthroscopic rotator cuff repair and subsequent tendon healing, focusing on challenges such as anchor fixation failure, intraoperative fractures, and limited surgical visibility. It examines how osteoporosis disrupts the tendon healing microenvironment post-surgery through mechanisms involving bone metabolism, growth factors, the immune system, sex hormones, oxidative stress, and adipose infiltration. Effective surgical planning is crucial to mitigate the adverse effects of osteoporosis on rotator cuff repair. This review offers recommendations for optimizing surgical strategies, including anchor selection, placement, and fixation techniques. In addition, it highlights the potential of anti-osteoporotic drugs and biological therapies to improve tendon-to-bone union and enhance clinical outcomes. For cases of inevitable repair failure, remedial strategies are proposed to inform clinical practice. A systematic literature search was conducted in the PubMed, Web of Science, and CNKI databases (2000–2025) using the following keywords: “osteoporosis,” “rotator cuff injury,” “shoulder arthroscopy,” “tendon-to-bone healing,” and “retear.” The inclusion criteria were as follows: (1) human or animal studies; (2) MRI-confirmed rotator cuff tears; and (3) full-text articles in English or Chinese. The exclusion criteria included case reports (n < 10).